From refusal letters to refusal letter generators – constancy and changeability in the form and content of German job application refusal letters - Szczęk, Joanna (Acta Universitatis Lodziensis. Folia Germanica, 2015)
The situation in the job market and specific expectations of job applicants lie at the heart of a peculiar “career” that has recently been experienced in refusal letters. Additional elements influencing their form and content are German law regulations. Aperitif-Briefe, Eisschreiben, and refusal letters proper are the three main variants of this text genre which has undergone noticeable evolution in the investigated period of 2001–2012. The aim of this article is to indicate the development stages of this text genre, paying special attention to the aids offered to refusal letter authors by developing technology, especially by media.